Clinical and Pathogenetic Characteristics and Diagnostic Criteria of Migraine in Patients with Nonspecific Connective Tissue Dysplasia - Shakirova Saodat Olimjon qizi; Rakhmatullayeva Gulnora Kutbiddinovna (Journal of Science in Medicine and Life, 2025)
Preliminary studies have shown that migraine is more common in patients with joint hypermobility syndrome (JHS). The aim of this study was to determine whether the prevalence, frequency, and disability of migraine differed between women with JHS and a control population. Twenty-eight patients with JHS and 232 controls participated in a cohort study. Participants underwent a structured interview and were diagnosed with migraine based on the criteria of the International Classification of Headache Disorders, 2nd edition. The primary outcome measures were migraine prevalence, frequency, and headache-related disability. Logistic regression was used for prevalence analysis, and Poisson regression was used for frequency and disability analyses. The results showed that the prevalence of migraine was 75% in JHS patients and 43% in controls. The adjusted odds ratio for migraine prevalence in patients with JHS was 3.19 (95% CI 1.24, 8.21).